Stuck in the mud - Dittmann, Sabine (Universidad de Costa Rica, 2002)
One had to be quick. Walk like a stork. Easier said than done, carrying a backpack full of equipment, buckets full of samples and a shovel over the shoulder, sinking knee-deep into the mud under the scorching tropical sun and watching out for crocodiles